Oral status, cognitive function and dependency among New Zealand nursing home residents. (23rd April 2018) - Thomson, William M.; Smith, Moira B.; Ferguson, Catherine Anna; Kerse, Ngaire M.; Peri, Kathryn; Gribben, Barry
Abstract : Objectives: To investigate clinical oral disease and its association with cognitive function and dependency among older New Zealanders in residential aged care. Material and methods: National survey of oral health in aged residential care throughout New Zealand. We classified residents into 1 of 3 levels of care: "low dependency care (or assisted living)"; "high dependency care"; or "specialist dementia care/psychogeriatric care." The Abbreviated Mental Test characterised cognitive function as "unimpaired" (scores of 7‐10), "moderately impaired" (4‐6) or "severely impaired" (0‐3). Intra‐oral examinations were conducted, along with a computer‐assisted personal interview. Results: Most of the 987 clinically examined participants were either at low or high dependency care level, with another 1 in 6 in psychogeriatric care. Almost half overall had severely impaired cognitive function. Just under half of the sample had 1 or more natural teeth remaining. Negative binomial regression modelling showed that the number of carious teeth was lower among women and higher among those who were older, those with more teeth and in those with severely impaired cognitive function. Oral debris scores (representing plaque biofilm and other soft deposits on teeth) were higher in men, those with more teeth, and in those with severely impaired cognitive function. Conclusions: Impaired cognitive function is a risk indicator for both dental caries and oral debris in aged residential care.